2007
DOI: 10.1161/hypertensionaha.107.094193
|View full text |Cite
|
Sign up to set email alerts
|

Self-Measurement of Blood Pressure at Home Reduces the Need for Antihypertensive Drugs

Abstract: Abstract-It is still uncertain whether one can safely base treatment decisions on self-measurement of blood pressure. In the present study, we investigated whether antihypertensive treatment based on self-measurement of blood pressure leads to the use of less medication without the loss of blood pressure control. We randomly assigned 430 hypertensive patients to receive treatment either on the basis of self-measured pressures (nϭ216) or office pressures (OPs; nϭ214). During 1-year follow-up, blood pressure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(101 citation statements)
references
References 32 publications
5
91
0
5
Order By: Relevance
“…However, although the use of home blood pressure may also reduce the intensity of drug treatment, it is unclear whether 24-h blood pressure control rates can be maintained. 23 Again using a high home blood pressure treatment target of 140 mm Hg for systolic and 90 mm Hg for diastolic blood pressure, Verberk et al 24 recently confirmed in a study of 430 participants with office hypertension that home blood pressure guided treatment may lead to less medication use, but this study also found significantly elevated 24-h blood pressure levels in the home blood pressure group. On the other hand, a small study among 98 participants with daytime ambulatory blood pressure of at least 85 mm Hg found similar blood pressure control rates whether antihypertensive therapy was adjusted based on home or 24-h blood pressure measurement.…”
Section: Discussionmentioning
confidence: 63%
“…However, although the use of home blood pressure may also reduce the intensity of drug treatment, it is unclear whether 24-h blood pressure control rates can be maintained. 23 Again using a high home blood pressure treatment target of 140 mm Hg for systolic and 90 mm Hg for diastolic blood pressure, Verberk et al 24 recently confirmed in a study of 430 participants with office hypertension that home blood pressure guided treatment may lead to less medication use, but this study also found significantly elevated 24-h blood pressure levels in the home blood pressure group. On the other hand, a small study among 98 participants with daytime ambulatory blood pressure of at least 85 mm Hg found similar blood pressure control rates whether antihypertensive therapy was adjusted based on home or 24-h blood pressure measurement.…”
Section: Discussionmentioning
confidence: 63%
“…4 Moreover, self-measurement of blood pressure increases adherence to antihypertensive treatment and allows reducing the number of clinic visits required for the diagnosis and treatment of hypertension. 6,7 The THOP (Treatment of Hypertension Based on Home or Office Blood Pressure) 8 and the HOMERUS (Home Versus Office Measurement -Reduction of Unnecessary Treatment) 9 trials demonstrated that adjustment of antihypertensive treatment based on HBP led to less intensive drug treatment with no differences in general well-being or target organ damage. However, no previous trial has assessed the long-term cardiovascular outcomes of antihypertensive therapy guided by self-measured HBP.…”
Section: Introductionmentioning
confidence: 99%
“…The first 15 participants who fulfilled the protocol criteria regarding sex and entry BP were included in the analysis of phase 1 (8 The use of the tested device was straightforward with no operational problems during the study. There was one failure of the device to record BP throughout the study, which was successful on repeated measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies found no difference between HBP and daytime ABP, [4][5][6][7] whereas others showed the HBP values to be higher 8 or lower, 9-11 particularly in children and adolescents. [12][13][14] Differences in BP levels between the two methods in these studies are attributed to intrinsic differences between the two methods, but also, at least in part, to the different devices used for each method (ambulatory and home monitoring).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation